Latitude and elevation as factors controlling occurrence of calanoid copepods in marginal lotic waters in New South Wales, Australia. Issue 6 (7th June 2018) - Kobayashi, Tsuyoshi; Miller, Jan; Bayly, Ian A. E.; Tang, Cheryl; Hunter, Simon J.; Ralph, Timothy J.; Stone, Luke
Abstract: Freshwater calanoid copepods develop abundant populations in lentic water bodies such as lakes, reservoirs and lagoons. In this study, we examined the potential habitat value of edges in lotic systems such as creeks and rivers where waters tend to stagnate, providing lentic‐like environments. We examined a total of 353 edge samples collected from 321 sites across the state of New South Wales, Australia, with latitudes in the range 28.3–37.4°S and elevations in the range 2–1834 m above sea level. Of the total samples examined, calanoid copepods were found in 94 samples, with the frequency of occurrences of species decreasing in the order: Boeckella fluvialis Henry, B. triarticulata (Thomson), Gladioferens spinosus Henry, G. pectinatus (Brady), B. major Searle, B. minuta Sars, and Calamoecia lucasi Brady. The probability of occurrence of the calanoid copepods was related negatively to both latitude (as absolute values) and elevation, based on logistic regression models. We conclude that the edges of many lotic systems provide additional habitats for some species of freshwater calanoid copepods, with constraints on their distributions along latitudinal and elevational gradients.